PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN (Studi Pada Hotel Timor Megah Kota SoE, TTS) - Donar W Selan; Juita L D Bessie (Journal of Management Small and Medium Enterprises (SMEs), 2019)
More and more manufacturers are involved in meeting the needs and desires of customers, causing each company to set orientation to customer satisfaction as the main goal. There is a tendency that customer satisfaction or dissatisfaction can be influenced by the quality of services provided by the company. This research was conducted at the Timor Megah Hotel Kota SoE, TTS Regency. The purpose of this study is to determine the effect of service quality that can be measured by several dimensions, including: tangibles, responsiveness, reliability, assurance, and empathy on customer satisfaction Timor Megah Hotel. The independent variable (X) of this study is the dimension of service quality consisting of tangibles (X1), responsiveness (X2), reliability (X3), assurance (X4), and empathy (X5). While the dependent variable (Y) of this study is customer satisfaction. The sampling technique used is the Accidental Sampling technique, with a total sample of 99 people with the criteria of having stayed more than twice and staying period for 4 years (2015-2018). Data collection techniques used were interviews, questionnaires and literature study. After the data is collected, the data is then analyzed using descriptive techniques and multiple linear regression. From the analysis it is known that tangibles, responsiveness, reliability, assurance and empathy simultaneously and partially have a significant effect on customer satisfaction. From the results of the analysis can also be made mathematical equations: Y = 3,568 + 0,150X1 + 0,245X2 + 0,209X3 + 0,192X4 + 0,362X5. The coefficient of determination obtained shows that 87.2% of the level of customer satisfaction is influenced by tangibles, responsiveness, reliability, assurance and empathy. Keywords: Tangibles, Responsiveness, Reliability, Assurance, Empathy and Customer Satisfaction.